THE ASSOCIATIONS BETWEEN HYPERTENSION AND STROKE FROM MAY MEASUREMENT MONTH AND BETWEEN NATIONAL HYPERTENSION PARAMETERS WITH STROKE MORTALITY FROM THE GLOBAL BURDEN OF DISEASE. (April 2021) - Lin, Queran; Ye, Tingxi; Beaney, Thomas; Poulter, Neil R.
Abstract : Objective: To characterise the association between stroke history and hypertension from the 2017 and 2018 May Measurement Month (MMM) blood pressure (BP) screening campaigns. To identify whether national-level MMM hypertension parameters are associated with national stroke mortality statistics. Design and method: Three BP readings and self-reported demographic, lifestyle and cardiovascular risk factors were collected from 2, 515, 578 participants in 95 countries. National stroke mortality statistics and Socio-Demographic Index (SDI) were extracted from the Global Burden of Disease (GBD) study 2017. Hypertension was defined as a raised BP (systolic BP > = 140 mmHg or diastolic BP > = 90 mmHg based on the mean of the second and third readings), or on antihypertensive medication. Multiple imputation using chained equations was performed to estimate mean BP readings where missing. Logistic and linear regression were applied, respectively, to the association between hypertension and stroke and between national-level GBD stroke mortality with MMM proportions with raised, treated and uncontrolled BP. Results: Low-middle-SDI countries in MMM had the highest age-sex standardised proportion of participants with a previous stroke (4.9%), compared with high-middle-SDI countries (1.4%). Globally, individuals with a history of stroke had a significantly higher mean BP than those without (6.6/1.7 mmHg higher, p < 0.001). Amongst post-stroke participants, antihypertensive medication appeared to mitigate the impact of lifestyle factors on the odds of hypertension. Stroke mortality increased, on average, by 34 per 100, 000 per 1% increase in the proportion of untreated individuals with raised BP (p = 0.006) and by 22 per 100, 000 per 1% increase in proportion with treated but uncontrolled BP (p = 0.003). Stroke mortality decreased, on average, by 14 per 100, 000 per 1% increase in the proportion of hypertensives treated (p = 0.01). Conclusions: Our study found suboptimal BP control among participants with a previous stroke globally, especially in low SDI countries. There was a significant association between national stroke mortality from GBD and the proportions of participants with raised or uncontrolled BP and of hypertensives treated in MMM. This suggests that despite lacking a population-based design, estimates from MMM broadly reflect rates of downstream mortality and that opportunistic screening can be an effective means of screening for hypertension.